Research on the logistics development level and spatial differentiation in node city with gray target decision model. Issue 1 (21st July 2020) - Qian, Wuyong; Wang, Lizhen; Wang, Jue; Chen, Qianqian
Abstract : Purpose: The purpose of this study is to master the development process and the construction effectiveness of backbone circulation network in an all-round way, formulate regional logistics development planning as well as promote the development of logistics industry by scientifically evaluating the logistics development of node cities with a view to analyzing their spatial differentiation features. Design/methodology/approach: In this paper, an integrated evaluation model is constructed by adopting factor analysis, gray target decision-making model based on cone volume and other methods so as to evaluate the logistics development of node cities. The dimensionality of three-dimensional panel data is reduced by factor analysis at first. Then, the gray target decision-making method based on cone volume is adopted to evaluate the development of node cities, whose evaluation results are carried out through the clustering analysis. The clustering analysis is used to determine the development level of node cities and to extract the spatial differentiation features of node cities. Findings: The results show that the proposed model can comprehensively evaluate the logistics level of node cities and clarify the overall logistics development and spatial differentiation of node cities, which could provide objective evidence for formulating national policies as well as promoting the balanced and coordinated development of regional logistics in China. Originality/value: The paper succeeds in overcoming the disadvantages of existing methods assessing the logistics development level, such as principal component analysis and factor analysis, which are not applicable to panel data.